"Bangladesh is not my country"" : the plight of Rohingya refugees from Myanmar. - Frelick, Bill; Human Rights Watch (Organization) ([New York, N.Y.] : Human Rights Watch, 2018)
"This report is based on a May 2018 visit to Cox's Bazar. Human Rights Watch found that the mega camp is severely overcrowded. The average usable space is 10.7 square meters per person, compared with the recommended international standard of 45 square meters per person. Densely packed refugees are at heightened risk of communicable diseases, fires, community tensions, and domestic and sexual violence. Bangladeshi authorities should relocate Rohingya refugees to smaller, less densely packed camps on flatter, accessible, nearby land within the same Ukhiya subdistrict where the mega camp is located, Human Rights Watch said."--Publisher website, viewed August 14, 2018.
"August 2018"--Table of contents page.
"This report was researched and written by Bill Frelick"--Page 65.
Includes bibliographical references.
Description based on online resource; title from PDF title page (viewed August 16, 2018)
Keywords: Refugee camps -- Bangladesh; Refugees -- Bangladesh; Refugees -- Burma; Rohingya (Burmese people) -- Bangladesh; Refugee camps; Refugees; Rohingya (Burmese people); Cox's Bāzār (Bangladesh); Bangladesh; Bangladesh -- Cox's Bāzār.; Burma